2004
DOI: 10.1002/jmri.20032
|View full text |Cite
|
Sign up to set email alerts
|

Correction of spatial distortion in EPI due to inhomogeneous static magnetic fields using the reversed gradient method

Abstract: Purpose: To derive and implement a method for correcting spatial distortion caused by in vivo inhomogeneous static magnetic fields in echo-planar imaging (EPI). Materials and Methods:The reversed gradient method, which was initially devised to correct distortion in images generated by spin-warp MRI, was adapted to correct distortion in EP images. This method provides point-by-point correction of distortion throughout the image. EP images, acquired with a 3 T MRI system, of a phantom and a volunteer's head were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
182
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(182 citation statements)
references
References 21 publications
0
182
0
Order By: Relevance
“…Solving this equation gives coefficients {p n }, from which we can find {z n } as roots of the polynomial in (16). Once {z n } are found, the corresponding unknowns {a n } can be easily computed by solving the following linear equation with a Vandermonde matrix Z:…”
Section: B Harmonic Retrieval Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Solving this equation gives coefficients {p n }, from which we can find {z n } as roots of the polynomial in (16). Once {z n } are found, the corresponding unknowns {a n } can be easily computed by solving the following linear equation with a Vandermonde matrix Z:…”
Section: B Harmonic Retrieval Methodsmentioning
confidence: 99%
“…Some other methods try to bypass estimation of the field map. For example, in [2] and [16] two images of the same object are acquired with preparation and readout gradients altered by some ratio α. The corrected image is produced by combining and rectifying these two acquired images pixel by pixel.…”
Section: Iω(r)t(k) E −T(k)/t *mentioning
confidence: 99%
“…Jezzard et al [7] have demonstrated that deformations due to B 0 field inhomogeneities appear mainly along the PED and are negligible in other directions. More precisely, we follow the distortion model as expressed previously in [17], [18] which assumes that I F and I B are generated from the theoretical corrected image C using a displacement field parallel to the PED:…”
Section: A Distortion Modelmentioning
confidence: 99%
“…This simple method strongly reduces the distortion, however it is sensitive to noise and the computed transformation needs to be smoothed, leading to a trade-off between regularity and precision. Other methods in this category include Morgan et al approach [18], using continuously alternating phase encoding, Weiskopf et al method [19] using a modified multi-echo EPI acquisition with reversed phases, or Holland et al algorithm [9] which performs an intensity-based registration (each line being considered independently). As for Voss et al algorithm, the obtained displacement field is sensitive to noise, especially when large displacements are present.…”
Section: Introductionmentioning
confidence: 99%
“…One simple algorithm compares two separate images acquired traversing k-space in opposite directions along the phase-encode (PE) direction (6). Other approaches use a field map measurement, since the displacement field at any given point is proportional to the susceptibility-induced change in B 0 (7).…”
mentioning
confidence: 99%